2021
DOI: 10.1111/rec.13496
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of the searching process in reviews of restoration outcomes

Abstract: In the recently declared United Nations Decade on Ecosystem Restoration (2021–2030), evidence‐based research has an essential role in summarizing restoration outcomes toward broad generalizations to advance restoration practice and science globally. However, to present trustworthy, high‐quality recommendations, evidence reviews should be based on rigorous methods that minimize bias and enhance systematicity, transparency, objectivity, comprehensiveness, and repeatability. To assess the current value of restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We searched for published studies of forest restoration that focused on seed dispersal functions as a key ecological process towards ecosystem restoration. For this review we followed Pickering and Byrne's (2014) recommendations for systematic quantitative approaches to literature reviews, and Romanelli et al (2021) for repeatability of reviews of restoration outcomes. Two global databases were selected to carry out our literature search: Web of Science and Science Direct.…”
Section: Methodsmentioning
confidence: 99%
“…We searched for published studies of forest restoration that focused on seed dispersal functions as a key ecological process towards ecosystem restoration. For this review we followed Pickering and Byrne's (2014) recommendations for systematic quantitative approaches to literature reviews, and Romanelli et al (2021) for repeatability of reviews of restoration outcomes. Two global databases were selected to carry out our literature search: Web of Science and Science Direct.…”
Section: Methodsmentioning
confidence: 99%
“…However, a gradual return of species can minimally guarantee ecosystem services provision, as relatively few species can sustain environmental health due to the high degree of functional redundancy and complementarity between species (Schoolmaster et al 2020). The standardization of metrics is also strongly recommended to increase both the repeatability and the reliability of restoration practices (Pander & Geist 2013; Romanelli et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions drawn from a meta‐analysis are highly dependent on the set of studies included. Following systematic review principles (Pullin et al, 2018), such as pre‐registering a protocol and thoroughly searching the literature, can help ensure reliable findings, yet these steps are often neglected in ecological meta‐analyses (Grames & Elphick, 2020; Romanelli et al, 2021). When designing our literature search (see pre‐registered protocol, Grames, Montgomery, et al, 2019 for full details), we identified three elements that needed to appear in papers as a minimum for them to be considered for our review: (1) a measure of either body condition or reproductive success, (2) a measure of invertebrate food availability or supplementation and (3) data from songbirds (Order: Passeriformes).…”
Section: Methodsmentioning
confidence: 99%